2017
DOI: 10.2106/jbjs.15.01340
|View full text |Cite
|
Sign up to set email alerts
|

Change in Talar Translation in the Coronal Plane After Mobile-Bearing Total Ankle Replacement and Its Association with Lower-Limb and Hindfoot Alignment

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…In addition to tibial component alignment, hindfoot alignment is also crucial to balance the ankle after TAR. Yi et al 36 assessed 159 ankles (153 patients) who underwent mobile-bearing TAR and found that a valgus hindfoot was related to medial translation of the talus. In the present study, varus hindfoot alignment at revision surgery was more frequent than valgus hindfoot alignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to tibial component alignment, hindfoot alignment is also crucial to balance the ankle after TAR. Yi et al 36 assessed 159 ankles (153 patients) who underwent mobile-bearing TAR and found that a valgus hindfoot was related to medial translation of the talus. In the present study, varus hindfoot alignment at revision surgery was more frequent than valgus hindfoot alignment.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the talus in the coronal plane was assessed via the talar center migration (TCM; Figure 2B). 36 Patients were divided into 3 similar-sized talar translation groups based on the mean preoperative TCM: lateral (>mean TCM + 0.4 * standard deviation [SD]), neutral (within 0.4 * SD from mean TCM), and medial (<mean TCM − 0.4 * SD). The hindfoot moment arm (HMA) was defined as the distance between the calcaneal and tibial axis (hindfoot alignment view; Figure 2C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6,14,22,28 Research has shown that the success of TAA highly depends on whether the surgeon is able to balance the hindfoot (eg, stable and neutral aligned). 23,29 In addition, accurate tibial and talar resection cuts, as well as a prosthesis design that restores native ankle biomechanics, were found to improve patient outcome and enhance the longevity of the implant. 15,16,27…”
mentioning
confidence: 99%
“…Coronal plane instability may occur over time, possibly resulting in soft tissue overload and cyst formation. 1,8,13,18,29 Theoretically, such complications could be avoided with the use of a fixed-bearing TAA system, as long as the position of the components is adjusted to the individual anatomy and kinematic of the ankle.…”
mentioning
confidence: 99%